METHODOLOGY FOR ORGANIZING CLINICAL TRIALS ON THE EFFECTIVENESS AND SAFETY OF CHINESE FIGURATIVE MEDICINE IN THE CONTEXT OF EVIDENCE-BASED MEDICINE - Martseniuk, V. P.; Lupenko, S. A.; Sverstiuk, A. S.; Pavlyshyn, A. V. (Medical Informatics and Engineering, 2018)
The article is devoted to the substantiation of the relevance of the development of a methodology for organizing clinical trials of the effectiveness and safety of Chinese figurative medicine in the context of evidence-based medicine. The paper considers the strategy of organizing and conducting clinical trials of Chinese figurative medicine. An information system for conducting clinical tests of Chinese figurative medicine has been developed.